(untitled) (Journal of the College of Basic Education, 2023)
This study was conducted in the Department of Science / College of Basic Education / Mustansiriyah University for the period from 12-15-2021 to 2-15-2022. The research aims to study the effect of the quality of feed, protein and vitamins added to the laying feed used in feeding table chickens and its relationship to productive performance and some traits. The quality of eggs such as egg weight, diameter and height of the yolk, histological study of the ovary, the weight of the ovary in each treatment, before and after the treatment. Non-laying or low-ovulation chickens were injected with FSH at a concentration of I.U / l 75. The effect of hormonal injections on productive performance and some qualitative characteristics was studied. For eggs, such as egg weight, diameter and height of the yolk, histological study of the ovaries, ovarian weight.In this study, 50 brown Lohmann chickens, 8-12 months old, were weighed individually and distributed into 5 groups as follows: The first group, the control, was fed only the diets of laying hens for the duration of the experiment. The second group (the first treatment) for a month was fed with diets for laying hens, to which vitamins and local protein were added, similar in shape to the diets, but different in composition and ingredients. The third group (the second treatment) for a month was fed with diets for laying hens, to which vitamins and protein powder (Swiss origin) were added, different from the composition and components of the local protein above. The fourth group (the third treatment) for a month of the experimental period was fed with diets of laying hens with wheat and barley The fifth group (the last hormonal injection): For a month of the experiment period, it was fed only laying hens diets. The results showed significant differences in the characteristic of egg production when calculating the general rate, as the production percentage for the second, third and fifth groups was was (73.3%, 66.6% and 83.3%), respectively. While the first and fourth treatments gave the lowest percentage of egg production in this comparison. The second and third treatment also gave the highest average egg weight when calculating the general rate compared to the rest of the treatments, as the average was 65 gm, and the average weight of the eggs of the fifth treatment (hormone) was 85 (gm). Significant differences appeared in the rates of egg weight in the five groups. It was also noted that there were differences In the rate of feed consumption, as a decrease was noticed in the quantities of feed consumed by the second and third treatment, and the highest rate of feed consumption was in the hormonal treatment, where it reached (200.5 grams / day / chicken), and the lowest consumption was in the control group, which reached (97.5 grams / day / chicken). Significant differences were seen in the diameter and height of the yolk of the five groups, and the largest diameter was in the hormonal treatment, reaching (0.20 ± 5.5 cm), and the highest height of the yolk in the first, second, and hormonal treatment, reaching (17 ± 0.33, 17 ± 0.25, 17 ± 0.50), respectively. And density in the texture of albumen, which indicates the giving of fodder and protein in appropriate quantities, which resulted in quality in the eggs produced in terms of weight and texture. The results of the dissection also showed the weight of the ovary and the number of eggs, mature follicles and yolks above the ovary increased in the first, second and hormonal treatment) and the largest weight of the ovary was in the treatment It reached (11.8 gm). It is clear from the current research that the type of feed, additives, nutritional supplements, and care for the hygiene and health of chickens have a great impact on obtaining high-quality productive characteristics in the produced eggs. , and the highest percentage of weight was in the hormone group, which reached (2600 ± 50 grams). Differences appeared in all treatments in relation to chicken weights, as the live body weight increased and the amount of change in body weight when calculating the general rate.